A study of 44 cases of pure dysgerminoma of the ovary: a single institutional experience - K., Sangeetha; Kumar, Ajay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The extent of surgery and additional therapy required in patients with dysgerminoma is debated. This study evaluated the clinicopathologic characteristics, treatment modalities, long-term survival, and menstrual and fertility outcomes of women with ovarian dysgerminoma managed at our institute. Methods: A total 44 histologically proven pure ovarian dysgerminoma cases were identified in this retrospective study. Patients who received treatment between 2006 and 2017 at Gujarat Cancer and Research Institute, either surgery or chemotherapy, or both were included. Results: About 60.6% of patients presented with stage I, 9.09% with stage II, 27.27% with stage III, and 3.03% with stage IV disease. Initial management was surgery followed by observation in 9 (20.45%), surgery followed by adjuvant chemotherapy in 25 (56.81%), and neoadjuvant chemotherapy (NACT) followed by interval debulking surgery (IDS) and adjuvant chemotherapy in 9 (20.45%) patients. Recurrence occurred in 1 (2.32%) patient with stage III disease after 1 year and 5 months (17 months) post-chemotherapy successfully salvaged with platinum-containing chemotherapy. The 3-year disease-free survival (DFS) and overall survival (OS) were 93.18% and 95.45%, respectively. Thirteen patients attempted conception and 6 (46.15%) delivered after treatment completion. Thirty-five patients underwent fertility-sparing surgery. Out of these, thirty patients (85.7%) got regular menstrual cycles. All three prepubertal girls attained menarche. Conclusions: Regardless of the stage, fertility-sparing surgery can be offered to the patient with good reproductive outcomes expected after fertility-sparing surgery followed by chemotherapy. Adjuvant chemotherapy is associated with significant improvement in DFS. NACT followed by surgery is a reasonable option for patients with advanced-stage dysgerminoma.